Restorative justice Approach to Certain Criminal Actions with the Threat of Under Five Years Prison in Functioning Criminal Law as Ultimum Remedium - Windy Rizky Putri; Erdianto Effendi; Zulfikar Jayakusuma (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2023)
The purpose of this research is to find out the concept of criminal law renewal to place restorative justice as ultimum remedium in certain crimes with a prison sentence of under five years. This type of normative legal research with the type of legal synchronization. Collecting data on normative legal research uses data collection techniques from a literature study. In drawing conclusions the author uses the deductive thinking method, namely a way of thinking that draws conclusions from a general statement or argument into a specific statement. the results of research and discussion can be concluded. First; The restorative justice approach to criminal acts with the threat of imprisonment for under five years finds its footing in the basic philosophy of Pancasila, namely in accordance with the 4th precept of Pancasila